Separation of essential oil from mixtures of melissa officinalis and cymbopogan citratus leaves for mosquito repellent - Ashwinder, Chelliah (2015)
Synthetic based chemicals such as DEET is one of the most commercialised synthetic based mosquito repellents. This compound is effective against a wide range of insects and arthropods but its usage has raised several concerns to human health and surrounding environment.To combat its negative effects, there has been an overwhelming interest of producing essential oil products from different species of natural plant materials in order to access their repellent properties.Essential oils are odourless volatile mixture of hydrocarbons and their repellent properties have been linked to the presence of monoterpenes and sesquiterpenes. Therefore, it is important to identify a best technique to extract the essential oil without causing significant effect on their chemical -constituents, since the conventional methods implied years back are time consuming and also record a low extraction yield.In order to enhance the extraction yield, an improvised approach namely Ultrasound Assisted Extraction-Hydrodistillation method will be exhibited to separate essential oil from mixtures of Mellissa officinalis and Cyinbopogan cifratus leaves. At the same time to evaluate the effectiveness of repelling properties in the essential oil, mixtures of leaves have been chosen in this extraction process.In this study, the effects of three main factors which are ultrasonic pre-treatment time, raw material to water ratio, and ultrasonic frequency were investigated.As a result, the best condition gives the highest yields of oil (0.3820%) were found at the ultrasonic frequency of 5kHz, pre-treatment time of 60 min and solid to water ratio of 1:6. The mixture ofMelissa officinalis and Cymbopogan citratus leaves reflects higher essential oil yield compared with the yield of Mellissa officinalisleaves. Finally the oil samples were analysed by using Gas Chromatography Mass Spectrometry (GC-MS). From the analysis, almost similar chemical compounds with potentiating repellent activity such as linalool, citronellal, geraniol, citral, a-pinene, and limonene were found in their respective essential oils. Anyhow, the amount it contains differs from one another. Moreover, the repellency test carried out using the extracted oil against mosquito have also showed positive outcome.